2017
DOI: 10.1038/srep40648
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Enhances DC to T-cell HIV-1 Transmission by Activating DC-SIGN/LARG/LSP1 Complex and Facilitating Infectious Synapse Formation

Abstract: DC-SIGN is a dendritic cell surface structure which participates in binding and transmission of HIV-1. Here, for the first time we demonstrate that cocaine induces over expression of DC-SIGN and significantly enhances virus transfer from DCs to T-cells by increasing the binding and internalization of HIV-1 in DCs. We found that cocaine activates a DC-SIGN mediated ‘signalosome’ complex by enhancing its association with LARG and LSP1. Further, LARG was observed to participate in DC-SIGN mediated internalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…activation (Anand et al, 2009;Prasad et al, 2017;Prasad et al, 2012). This study, thus, support our findings highlighting the key role of LSP1 in the regulation of focal adhesion dynamics and cell migration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…activation (Anand et al, 2009;Prasad et al, 2017;Prasad et al, 2012). This study, thus, support our findings highlighting the key role of LSP1 in the regulation of focal adhesion dynamics and cell migration.…”
Section: Discussionsupporting
confidence: 91%
“…In this context, it has been shown that the human immunodeficiency virus can induce migration of dendritic cells (Anand et al, 2009). These viruses control dendritic cell migration by the binding of their envelope protein gp120 to DC-SIGN on dendritic cells (Prasad et al, 2017;Prasad et al, 2012). Remarkably, gp120-DC-SIGN interaction triggers a signalling cascade that involves LSP1 and leads to Rho GTPase (a regulator of focal adhesion dynamics)…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine has been shown to synergistically enhance the pathologic processes induced by HIV infection [2325]. Cocaine is also known to induce oxidative stress, tight junction disruption, endothelial cell inflammation dysfunction, and loss of BBB integrity [26–28].…”
Section: Discussionmentioning
confidence: 99%
“…Besides being essential for the formation of the synapse, DC-SIGN binding to HIV-1 particle in the first place also sets a signaling cascade that favors the trans-infection pathway over productive infection or viral degradation. DC-SIGN is known to associate with LARG, whose activation promotes activation of RhoA and the focal adhesion molecules FAK, Pyk2, and paxillin, all of them structural components of the infectious synapse (199).…”
Section: Role Of Dendritic Cells In Hiv-1 Infectionmentioning
confidence: 99%